Natural and Anthropogenic Drivers of Variation in Bumble Bee Gut Microbiotas - Hotchkiss, Michelle (Université d'Ottawa | University of Ottawa, 2024)
Bumble bees are key pollinators in natural and agricultural ecosystems. Like all social bees, their health is supported by a core gut microbiota consisting of a few, specialized bacterial phylotypes. The composition and community structure of bumble bee gut microbiotas can vary in response to natural and anthropogenic factors, which may impact its ability to support host health and performance. My thesis characterizes variation in bumble bee gut microbiotas caused by anthropogenic drivers, like pesticide exposure, and natural factors, like diapause and host species. In Chapter 2, I qualitatively and quantitatively synthesized literature on pesticide-induced disturbances in bee gut microbiotas. I found that core phylotypes vary in their susceptibility to pesticide-induced disturbance, and that pesticide concentration, exposure duration, and concurrent stressors all influence whether and how bee gut microbiotas are disturbed. I also identified gaps in our knowledge of pesticide-bee gut microbiota interactions, some of which I addressed in Chapter 3. There, I found that exposure to the fungicide chlorothalonil for a short, field-realistic duration did not alter bumble bee fecal microbiota community structure regardless of concentration, and that fecal microbiota structure did not accurately reflect gut microbiota structure. In Chapter 4, I characterized shifts in queen bumble bee gut microbiotas during diapause, an important stage in the bumble bee colony life cycle. I found that during diapause microbial abundance fell by an order of magnitude and gut microbial communities underwent dramatic restructuring, with some core phylotypes becoming undetectable past diapause onset. Finally, in Chapter 5 I examined how bumble bee gut microbiota composition and function vary with host species and origin (i.e., whether bees come from wild or commercial populations). I found that gut microbiota community structure varied between bumble bee species, between commercial and wild populations within the same species, and between populations from different commercial suppliers. However, despite this variation in community structure, gut microbiota metabolic potential was largely consistent across all hosts, including for metabolic capabilities related to host performance. Altogether, my thesis makes significant contributions to understanding variation in the gut microbiotas of a key, native pollinator and provides a strong foundation for future studies on this fascinating symbiosis.
Keywords: bumble bee; gut microbiome; pesticide; diapause; social bee gut microbiome; commercial bees; wild bees